2023
DOI: 10.1001/jamainternmed.2023.0144
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Cognitive Trajectory in Older Adults Following Major Surgery and Delirium

Abstract: ImportanceThe study results suggest that delirium is the most common postoperative complication in older adults and is associated with poor outcomes, including long-term cognitive decline and incident dementia.ObjectiveTo examine the patterns and pace of cognitive decline up to 72 months (6 years) in a cohort of older adults following delirium.Design, Setting, and ParticipantsThis was a prospective, observational cohort study with long-term follow-up including 560 community-dwelling older adults (older than 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The primary outcome of this study was an initial diagnosis of post‐ICU dementia within 5 years after ICU hospitalization. This timeline was longer than previous ICU survivor studies which examined cognition for about 1 year after ICU hospitalization, because other cohort studies examining delirium in non‐ICU settings, most notably the Successful Aging after Elective Surgery study, showed cognitive decline as long as 6 years after hospitalization 28 . Initial diagnosis of post‐ICU dementia was defined as the initial coding in the EMR of any of the International Classification of Diseases (ICD)‐9 and ‐10 codes for AD dementia and other related dementias (Table S1A in supporting information) or being prescribed medications for dementia (Table S1B).…”
Section: Methodsmentioning
confidence: 83%
“…The primary outcome of this study was an initial diagnosis of post‐ICU dementia within 5 years after ICU hospitalization. This timeline was longer than previous ICU survivor studies which examined cognition for about 1 year after ICU hospitalization, because other cohort studies examining delirium in non‐ICU settings, most notably the Successful Aging after Elective Surgery study, showed cognitive decline as long as 6 years after hospitalization 28 . Initial diagnosis of post‐ICU dementia was defined as the initial coding in the EMR of any of the International Classification of Diseases (ICD)‐9 and ‐10 codes for AD dementia and other related dementias (Table S1A in supporting information) or being prescribed medications for dementia (Table S1B).…”
Section: Methodsmentioning
confidence: 83%
“…Together with the loss of gray matter volume after episodes of POD, 36 our findings could represent the structural correlate of worsening cognitive trajectories in POD patients. 37 Future studies need to investigate whether this white and gray matter depletion after episodes of delirium may lead to cognitive decline and eventually the development of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Delirium's adverse impact is profound including functional decline, accelerated cognitive decline, prolonged hospitalization, and higher healthcare costs (approximately $32.9 billion nationally per year) 5,6 . The development of delirium serves as a marker of brain vulnerability, and postoperative delirium has been associated with 40% accelerated cognitive decline 72 months following surgery 6,7 . However, the pathophysiological pathways linking delirium to dementia remain unclear 8 …”
Section: Introductionmentioning
confidence: 99%
“…5,6 The development of delirium serves as a marker of brain vulnerability, and postoperative delirium has been associated with 40% accelerated cognitive decline 72 months following surgery. 6,7 However, the pathophysiological pathways linking delirium to dementia remain unclear. 8 We previously conducted the Successful Aging after Elective Surgery (SAGES I) Study following a cohort of over 560 older adults undergoing surgery.…”
Section: Introductionmentioning
confidence: 99%